What future for family farming in ACP countries? - Neun, Hansjorg; Mikos, Philip (2006)
Agriculture remains critical to poverty reduction and growth in most ACP countries, hence it has to raise higher on the development agendas. Family farming has proved to be amazingly resistant in hostile conditions, but the sector still urgently requires